CASHLESS SOCIETY: TANTANGAN DAN KESIAPAN PEDAGANG PASAR TRADISIONAL DI KOTA DENPASAR - Prasetia, Putu Bagus Wedanta; Lestari, Ni Putu Nina Eka (Buletin Studi Ekonomi, 2023)
This research was conducted to determine the challenges and readiness of traditional village market traders in implementing a non-cash payment system. This research was conducted using a qualitative approach to the research location in Nyanggelan Market, Panjer Traditional Village. Informants in this study were market heads, banks and buyers or traders in the Nyanggelan market who had used a non-cash payment system. The results of this study indicate the readiness of the Nyanggelan market traders to use a non-cash payment system supported by the market digitization program, but there are still many traders who do not understand using a non-cash payment system.